Laying the Foundation for Policy: Measuring Local Prevalence for Autism Spectrum Disorder - Carolyn Dudley; Jennifer D. Zwicker (The School of Public Policy Publications, 2016)
WHY IS THIS AN IMPORTANT ISSUE? Autism Spectrum Disorder (ASD)1 is the most common neurological condition diagnosed in children in Canada. Estimates of prevalence are reported as national numbers but may not reflect local numbers and consequently local needs. Local and provincial ASD prevalence estimates can be used by policy makers to inform local service delivery, resource allocation and future planning. WHAT DOES THE RESEARCH TELL US? ASD prevalence is on the rise Estimates of ASD prevalence in Canada have risen dramatically over the past several decades.2 The reason for the dramatic rise is uncertain and may be a result of a combination of a true rise in incidence, changing diagnostic criteria and increased awareness.3 It has been speculated that Alberta may have higher numbers of persons with ASD due to family in-migration to utilize higher levels of funding for ASD supports compared to other provinces.4 Prior to this study, there were no prevalence estimates for Alberta to assess this theory. A better understanding of Alberta ASD prevalence is critical as these estimates assist policy-makers, clinicians and educators in planning for school supports, adult day programs, employment programs, housing options and other programs essential to enhancing quality of life for individuals living with ASD and their families.